VERSE INTERPRETATION OF THE BASIC MANAGEMENT PROCEDURE - Rahmat Hidayat; Nanda Miranda; Ravika Hadi; Askur Amin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
Al-Qur'an as the main guideline for mankind, every activity carried out by humans should refer tothese guidelines. Education management is no exception. In its implementation, educational management should refer to the principles. The Koran does not deny the existence of educationalmanagement principles, including those stated in the Qur'an, namely: faith, sincerity, ihsan, exemplary, unity of direction, deliberation, accountability. , efficient and effective, participatory,responsible, competent, and flexible and cooperative. This type of research is research literature (library research) and included in the category of qualitative research with thematic methods (maudu'iy). technicalanalysis of data in this study using content analysis (content analysis). Content analysis is a research techniquefor making inferences that can be replicated and with valid data, taking into account the context.